2019
DOI: 10.1101/868406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An implicit memory of errors limits human sensorimotor adaptation

Abstract: 22In many forms of motor adaptation, performance approaches a limit at which point learning stops, 23 despite the fact that errors remain. What causes this adaptation limit? Here we found that while reach 24 adaptation exhibited an asymptotic limit, this limit was not fixed: when the variance of the perturbation 25 decreased, the adaptation limit increased, and performance improved. Moreover, the limit could be 26 altered in real-time by changing perturbation variance. The same was true at low reaction times, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 84 publications
7
52
3
Order By: Relevance
“…Lastly, we do not claim that other mechanisms affecting learning do not contribute to asymptotic behavior (Albert et al, 2019), or that a state-space model with gradual decay towards zero is generally invalid (Brennan & Smith, 2015). What we suggest is that one potentially major aspect determining the magnitude of asymptotic errors is a speed accuracy trade-off.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Lastly, we do not claim that other mechanisms affecting learning do not contribute to asymptotic behavior (Albert et al, 2019), or that a state-space model with gradual decay towards zero is generally invalid (Brennan & Smith, 2015). What we suggest is that one potentially major aspect determining the magnitude of asymptotic errors is a speed accuracy trade-off.…”
Section: Discussionmentioning
confidence: 65%
“…A new approach to the state-space model is that residual errors in adaptation paradigms are caused by implicit processes that tune the sensitivity to errors until it reaches the equilibrium with constant forgetting (Albert et al, 2019). The authors in this recent study manipulated the variability of the perturbation and found that residual errors increase with the perturbations' variance.…”
Section: Discussionmentioning
confidence: 99%
“…If implicit and explicit systems share an error source, each system's current response can be shaped not solely by past experience, but also by changes in the other system. This may explain a potential disconnect between studies that have suggested that experience-dependent increases in learning rate are subserved solely by flexible explicit strategies 28,[33][34][35][36] , and studies that have pointed to concomitant changes in implicit learning systems 17,37,38 .…”
mentioning
confidence: 94%
“…Another possible disadvantage of implicit optimization is that many have found adaptation that relies solely on an implicit process will be incompleteeven after many trials, residual errors, or an asymptotic offset, persist (Albert et al 2020;Bond and Taylor 2015). Albert et al (2020) demonstrated that this offset is a signature of implicit learning and its magnitude relates to one's sensitivity to past errors. In our experiment, our inability to precisely identify the energy optimal gait makes it difficult to determine if adaptation was incomplete.…”
Section: Discussionmentioning
confidence: 99%